PLANT CELL CULTURE - D E EVANS. et al (LONDON BIOS SCIENTIFIC PUBLISHERS TAYLOR & FRANCIS GROUP, 2003)
Plant cell culture is an essential methodology in plant sciences, with numerous variant techniques depending on the cell type and organism. This book provides the reader with a concise overview of these techniques, including basic plant biology for cell culture, basic sterile technique and media preparation, specific techniques for various plant cell and tissue types including applications, tissue culture in agriculture, horticulture and forestry and culture for genetic engineering and biotechnology.
Keywords: PLANT CELL CULTURE